2007
DOI: 10.1007/s11071-006-9167-0
|View full text |Cite
|
Sign up to set email alerts
|

Attractors of harmonically forced linear oscillator with attached nonlinear energy sink I: Description of response regimes

Abstract: A series of two papers is devoted to detailed investigation of the response regimes of linear oscillator with attached nonlinear energy sink (NES) under harmonic external forcing and assessment of possible application of the NES for vibration absorption and mitigation. The first paper of the series is devoted to analytic and numeric description of the attractors (response regimes) of the system. Analytic approach is based on averaging and multiple-scales analysis, the mass ratio being used as the small paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 16 publications
2
122
0
Order By: Relevance
“…For a system with one tube only, as studied before [7,8], a harmonic excitation can produce a strongly modulated response, indicating an alternation of modes corresponding successively to resonance build up and TET. For more complicated systems, the analysis is less easy but the same ideas can be considered as a basis of reflection.…”
Section: Dissipated Power In Smrmentioning
confidence: 91%
See 1 more Smart Citation
“…For a system with one tube only, as studied before [7,8], a harmonic excitation can produce a strongly modulated response, indicating an alternation of modes corresponding successively to resonance build up and TET. For more complicated systems, the analysis is less easy but the same ideas can be considered as a basis of reflection.…”
Section: Dissipated Power In Smrmentioning
confidence: 91%
“…Weakly quasi-periodic responses and strongly quasi-periodic responses (also named "strongly modulated responses") can exist or coexist [7,8]. The very important point is that this peak reduction can occur in a wide frequency band, with the NES adapting itself to the resonance frequencies of the primary system.…”
Section: Introductionmentioning
confidence: 99%
“…The complexification method combined to the averaging method will be applied starting from the equations of motion (7)(8).…”
Section: Complexified Systemmentioning
confidence: 99%
“…Weakly quasiperiodic responses and strongly quasiperiodic responses (also named "strongly modulated response") can exists or coexist [7]. The very important point is that this peak reduction can occur in a wide frequency band, with the NES adapting itself to the resonance frequencies of the primary system.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [6] studied the system with nonlinear damping and nonlinear springs, they found that a reduction of the vibration amplitude can be obtained by adjusting the parameters of the nonlinear dampers, nonlinear spring stiffness and excitation frequency. It has also been demonstrated [7][8][9][10] that the primary phenomena behind the energy pumping produced is due to resonant interactions between coupled linear and nonlinear components.…”
Section: Introductionmentioning
confidence: 99%